Kazakh society: the search for identity in the global cultural process (Journal of Philosophy Culture and Political Science, 2018)
This article discusses some aspects of the culture as the essential basis of Kazakhstan’s development model. The peculiarities of the national idea of Kazakhstan. Spotted and the necessity of further development of National Unity . Formulated the concept of « unity in diversity « is the basic ontological principle deploying Kazakhstan culture being in the flow of contemporary cultural and social processes. Based on the research in Kazakhstan today also felt decisive shift , there are even quite conscious calls for cultural revival , as if not the only , the main thing that can help in reviving the nation. Thus, in modern conditions Eurasian idea actualized even more, it is the only alternative to the threat posed by the development of the world toward unilateralism. Kazakhstan supports strengthening Eurasian unity for movement toward multipolarity. Key words: national idea, Kazakhstan, euroislamic dialogue, unity, globalization, sovereignty, cultural identity, traditions are Eurasian integration.